Análise do acesso e acessibilidade da estrutura das Unidades Básicas de Saúde no Brasil: Programa Nacional de Melhoria do Acesso e da Qualidade na Atenção Básica (PMAQ-AB) - PINHO, Ellen Christiane Corrêa (2020)
The Basic Health Unit is the preferred gateway for SUS, has a privileged space for managing care of people and plays a strategic role in the care network. Therefore, monitoring and evaluating its performance and its structural conditions is essential to measure its reach and quality, in order to contemplate the access and accessibility of the population that needs differentiated care. The study evaluated the access and accessibility of the structure of the Basic Health Units by regions of Brazil, analyzing whether they are in accordance with the recommendations of the National Policy for Primary Care. This is a descriptive and cross-sectional study based on data from the 3rd cycle of PMAQ-AB. A total of 30.346 Basic Health Units (BHU) in Brazil were evaluated. In the Infrastructure component, 21,7% have a standard operating structure that differs from that established for a UBS. Of the units evaluated, 8% did not present any type of signaling. The North region had the worst performance for information available to users and for accessibility indicators, with one exception on tactile floor for accessing unit facilities. Regarding the Organizational component, 84,4% have a fixed opening hours. It is noteworthy that in all regions of Brazil there were only 450 units operating on Saturdays and 196 on Sundays. And only 46,3% of the units maintain all their activities at lunch time. The results of this study allowed us to identify and analyze the organizational and infrastructure components of the basic health units in Brazil. There was a disparity in the findings found nationwide, demonstrating regional differences in access and accessibility, which underscores the need for progress. In the overall assessment, the organizational component of the structure points to compliance with the recommended. In the infrastructure component, accessibility indicated percentages that demand advances, a factor that directly interferes with user access to public health services.